Analysis of Slope Stability and Disaster Law under Heavy Rainfall. (23rd February 2021) - Guo, Pengfei; Yuan, Yadi; Peng, Yanyan; Zhang, Haijiag; Zhao, Yongxu
Abstract : Based on this, the slope stability and disaster law under the condition of heavy rainfall are studied. With the slope of Shangge Village as the background, the slope stability under the condition of heavy rainfall is deeply studied through theoretical analysis, laboratory physical model experiment, and numerical simulation. Results showed that due to the heavy rainfall within 2 h, the deformation of the slope is not obvious in the rain 2 h 7 h period, first of all in the position of slope toe of slope stress raiser; As the rainfall continued, the infiltration of rainwater led to weakening of the rock mass strength, and the cracks in the slope fracture zone further expanded and extended to the top of the slope. After 7 hours of rainfall, the slope formed a sliding surface. The physical model experiment and the numerical simulation results are in good agreement, which can provide the basis for slope reinforcement under heavy rainfall conditions and have important scientific significance and social value for the reasonable site selection of housing construction, transportation network, and disaster prevention and mitigation in coastal areas.